No haven: the Connecticut mob and the rise of America's model city - Bleakley, Paul (Rowman & Littlefield, 2024)
"Boston to the north and New York City to the south, Connecticut's history of organized crime is often overlooked. Here's the untold story of New Haven's illegal past"--